PENERAPAN TATA KELOLA YANG BAIK (GOOD GOVERNANCE) PADA PRIMER KOPERASI PEGAWAI UPN “VETERAN” YOGYAKARTA - Lindary Devi Yohsica Tanggulungan; Sutoyo Sutoyo; Indra Kusumawardhani (Program Magister Akuntansi Unsyiah, 2014)
This research was conducted to understand the implementation of good governance on Primer Koperasi Pegawai UPN “Veteran” Yogyakarta. Cooperative is economic organization that based on sense of family. employee's Cooperative in the present society with the purpose to achieve the welfare of members and society with professionalism, quality and integrity. This type of research is a qualita tive descriptive method. Instruments used in data collection are interviews, observations, documentations and questionnaires.The result of the research represent passage of the good governance principles include of transparency in the provisioning information for supervisors, administrators, managers, employees, members in a transparent and opened, so that employees have already known how the system that are within the cooperative principle accountability. The principle of responsibility shown Primer Koperasi Pegawai UPN “Veteran” Yogyakarta towards employees by providing a range of benefits, health insurance, safety and social responsibility to the society. Then the principle of independency showed no intervention internally and externally. Finally, the Fairness principle, shareholders (members) receive fair and same treatment in the implementation of the RAT and the division SHU, employees were recruited based on their expertise, so the company does not discriminate towards employees based on racial and establish a fair system of reward and punishment. Good Governance in Primer Koperasi Pegawai UPN